تداخل الأجناس الأدبية في الرواية العربية المعاصرة - قماز, أحلام; بلعلوي, سعيدة; سعيد, شمسة (جامعة الوادي - University of Eloued, 2023)
. تعد قضية الأجناس الأدبية من أقدم القضايا التي تناولتها نظرية الأدب فقد ظهرت مند الإرث اليوناني . نظرية الأجناس نظرية غربية, و يعد أرسطو واضع الأسس الأولى لها. . الرواية من أكثر الأجناس الأدبية عرضة لتداخل الأجناس و تمازجها باعتبارها الجنس الأكثر تحرر وانفتاح, فرواية " موت صغير " انفتحت على: . السرد: فتمثل السرد في تلك الوقائع و الأحداث التي ينقلها الراوي للمتلقي . . أدب الرحلة: لقد أضفى هذا الأدب نوع من التواصل و الحوار بين الأدباء و العلماء و رجال الدين و تبادل الأفكار و أخد الفائدة. . التناص : فقد استمد الروائي سيرة ابن عربي من الكتب و المصادر التاريخية. . الحكمة : فقد جاءت لجدب انتباه القارئ. . الخطبة : وظفت لإرسال رسالة معينة للسامع. . الشعر : فوضفت الكتابة أشكالا من تداخل الشعر كاللغة الشعرية و النصوص الشعرية لها و آخرين The issue of literary genres is one of the oldest issues dealt with by literary theory, as it appeared since the Greek legacy .The theory of races is a Western theory, and Aristotle is considered the founder of the first foundations for it. . The novel is one of the literary genres most prone to overlapping and mixing genres as it is the most liberating and open genre. The novel "A Small Death" opened to: . Narration: The narration is represented in those facts and events that the narrator conveys to the recipient. . Literature for the Journey: This literature has added a kind of communication and dialogue between writers, scholars and clerics, exchanging ideas and taking advantage. . Intertextuality: The novelist derived the biography of Ibn Arabi from books and historical sources. . Wisdom: It came to attract the attention of the reader. . Sermon: used to send a specific message to the listener. . Poetry: Writing added forms of intertwining poetry, such as poetic language and poetic texts for it and others.
أدب حديث ومعاصر
Keywords: : تداخل _ الأجناس _ الأدبية _ الرواية _ المعاصرة; Overlap- races-literary-the nove